2020
DOI: 10.3389/fnagi.2020.00034
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Characterization and Biomarkers of Age and Sex Differences in the Decline of Spatial Memory

Abstract: The current longitudinal study examined factors (sex, physical function, response to novelty, ability to adapt to a shift in light/dark cycle, brain connectivity), which might predict the emergence of impaired memory during aging. Male and female Fisher 344 rats were tested at 6, 12, and 18 months of age. Impaired spatial memory developed in middle-age (12 months), particularly in males, and the propensity for impairment increased with advanced age. A reduced response to novelty was observed over the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 149 publications
(199 reference statements)
1
50
0
1
Order By: Relevance
“…The decline of cognitive function is a well-characterized feature of increasing age. Learning and memory, which are constituent characteristics of cognitive functions, decline not only in human but also in rats, starting from 12 months of age 38 . Barnes maze was used to measure the latency period required by the rats to escape through the right hole into an escape box.…”
Section: Cognitive Functionmentioning
confidence: 99%
“…The decline of cognitive function is a well-characterized feature of increasing age. Learning and memory, which are constituent characteristics of cognitive functions, decline not only in human but also in rats, starting from 12 months of age 38 . Barnes maze was used to measure the latency period required by the rats to escape through the right hole into an escape box.…”
Section: Cognitive Functionmentioning
confidence: 99%
“…It is well established that the frequency bandwidth of spontaneous BOLD signal oscillations falls within previously characterized infraslow frequencies (<0.5) that cover a large expanse of rat cortex (60,61). Studies in primate visual cortex have also shown that normalized spectral frequencies in the band limited power for gamma (40-100Hz) share a high degree of statistical dependency (mutual information) with the fMRI BOLD signal while alpha (8)(9)(10)(11)(12) Hz), beta (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and higher frequency (0.9-3kHz) multi-unit activity much less so (62).…”
Section: Discussionmentioning
confidence: 81%
“…The paradigm used here did not generate a memory 'response' by the rats prior or after scanning and this weakens the direct linkage between the network differences between groups and their role in memory structure in the brain. Regarding the experimental paradigm itself, we have previously applied better validated and more system selective experimental paradigms for assessing learning and memory that allowed a priori hypothesis testing of the brain regions involved in memory processing (20,21). We anticipate future studies using similar paradigms here but with the added modification that the memory-retrieving process or the memory-signaling behavior be carried out or measured during a short temporal delay prior to imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cortex, thalamus, striatum, and amygdala 19 . In a study using optimal percolation theory to quantify the collective influence of hub nodes in male rat fMRI networks, Del Ferraro et al observed that hippocampal CA3-CA1 long-term potentiation (LTP) caused a potent global integration of brain BOLD activation which was weakened by elimination of a low degree node such as the nucleus accumbens 20 .…”
mentioning
confidence: 99%